Internal Migration and Poverty Reduction in Ghana (International Journal of Technology and Management Research, 2020)
Nowadays, policymakers and researchers are discussing the relationship between internal migrations on poverty reduction. The uneven economic developments in Ghana these days, among others, have made the essential towns a des tination for internal migrants from other areas of the country. This study examines internal migration that acts as a way o ut of area poverty where conservative strategies on poverty reduction have failed to draw on empirical evidence on Ghana's civil movement. It is also examining how internal migration leads to economic development in rural areas. For the migrants a proportionate sample size of 680 used. Snowball sampling utilized for population selection (migrants) Gathered data from six regions and 38 districts in Ghana.It was analysed using questionnaires and interviews using versi on 22 of the Social Sciences Statistical Package (SPSS). The research also used statistical methods such as multinomial re gression, Spearman rank analysis of correlation, and ordinal model regression. Internal migration has a positive effect on poverty alleviation in Ghana bringing good drinking water supplies, electricity expansion, sanitation facilities, improved incomes, better healthcare, better nutrition, savings and investment opportunities to migrants, their families and communities among others. In order to maximize the effect of internal migration, the study recommended policy, theoretical and practical interventions on poverty reduction in Ghana
Keywords: Training; Employees’ training; Performance; Employees’ performance